An investigation into the cost-sharing mechanism of order agriculture with consideration for green investment - Honglin Hu; Ouyang Dai; Ligong Qin; Jun Li (Cogent Food & Agriculture)
The "processing company + farmer" model is studied for its wide - applicability, targeting high production costs and low farmer participation in green agriculture. Using game theory, we build a model to analyze cost - sharing mechanisms’ effects on green production levels and stakeholders’ profits. Model analysis shows that such a mechanism boosts both processing companies’ and farmers’ profits. Specifically, farmers’ profits rise by 20%, and companies’ by 8%. Higher agricultural product conversion rates amplify this profit growth. This indicates cost - sharing mechanisms’ economic benefits and their role in motivating farmers for green production. In summary, for the "processing company + farmer" model, a cost - sharing mechanism is crucial for profitability and promoting farmer - led green production, supporting sustainable agriculture.